Психологічні аспекти переходу російськомовних українців на українську мову - Гончарова, К. С. (ХНУРЕ, 2023)
During the war, the transition to the Ukrainian language is of particular importance, but for russian-speaking Ukrainians it can be a psychological process. Language is a habit that explains certain difficulties when transitioning from one language to another. The transition to the Ukrainian should be a systematic phenomenon and be accompanied by cultural and linguistic measures that will help russian-speaking Ukrainians learn the Ukrainian language. The article provides psychological and pedagogical recommendations for this process.